Teacher Perceptions toward Professional Learning Community on the Development of Thai Students’ 21st Century Skills - Wittaya Worapun,; Sinthawa Khamdit,; Pinsuda Siridhrungsri, (Journal of Educational Issues, 2024)
The 21st century skills are important matters in education management in the upcoming era, and they need cooperation among stakeholders of an educational context to be developed. The purpose of the study is to study teacher perceptions toward professional learning community (PLC) in developing 21st century skills of students in Thailand. The samples were 1154 teachers from 376 schools in 17 provinces selected by a purposive sampling method in Thailand. The instruments were a professional learning community activity among teaching staff in the school and a questionnaire for teachers’ perception of the method. The data were analyzed using percentages, mean scores, and standard deviation. The results of the study indicate that the perception of teachers on students’ 21st century skills after the PLC was at a high level (x̄ = 4.30) and higher than before the PLC which was at an average level (x̄ = 3.15). The results of the study could be summarized to indicate the positive perception of teachers in using the professional learning community as a school managerial method in developing skills and morality of the 21st century. It could also be concluded that collaboration and idea-sharing among teaching staff and administrators were the keys to success. Therefore, the results of the study could be implicated in school management that aims to develop students’ 21st century skills.